Drivers of corporate rebranding in the telecommunications industry in South Africa and the impact on brand equity - Moloko, Katse Rodney (My University, 2014)
In the last two decades, South Africa has witnessed a series of reforms in the telecommunications industry, including the corporate rebranding efforts undertaken by major telecommunications corporates. In April 2011, Vodacom, following the increase in ownership in 2009 by Vodafone, launched its new image. With the corporate rebranding, Vodacom kept its name, but effected changes to the logo, slogan and colour scheme. The rationale for keeping the name is the fact that Vodafone’s presence in Africa is far smaller than Vodacom’s. Vodacom holds power and position in the marketplace in South Africa and Africa. In addition to changing its brand colours from the familiar green and blue to red, the brand colour of UK-based Vodafone, which owns 65 percent of Vodacom, it has also assimilated Vodafone’s teardrop logo. The purpose of this research was to investigate the drivers of corporate rebranding and the impact of corporate rebranding on brand equity of South African brands. The research used quantitative data. There were 134 respondents, with 109 completed questionnaires, from a convenience sample who were all employees of Vodacom. The survey was administered through an online portal and analysed using descriptive statistics and principal component analysis. The main findings confirmed 9 of the 10 drivers of corporate rebranding identified in previous literature. The outcome of the research also summarised these drivers into 2 fundamental factors, namely corporate structure and strategy, and macroeconomic factors. The brand equity of the Vodacom brand has been adversely impacted following a rebranding exercise. The old brand is represented by three factors that corresponded with Aaker’s model (Aaker, 1991). These factors are brand awareness, perceived quality and brand loyalty. The new brand was represented by a factor labelled ‘infant brand’. Macroeconomic factors were perceived to the most significant drivers of corporate rebranding.
Thesis (M.M. (Strategic Marketing))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.
Keywords: Branding; Rebranding; Vodacom; Vodafone; Corporate rebranding; Brand equity